The Effectiveness of Neuromuscular Taping (NMT) Application and Core Stability Exercise to Increase Agility in the Case of Jumpers Knee at PTPN V Pekanbaru Soccer School University Abdurrab - Muawanah, Siti (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2022)
Jumper's knee occurs when there is repeated pressure and pulling in the jumping motion causing pathology in the knee which is caused by the tendons attached to the bottom of the patella experiencing irritation, many factors including the continuous pulling on the patella. The purpose of this study was to assess the effectiveness of the application of Neuromuscular Taping and Core Stability Exercise to increase agility in the condition of jumpers knee conditions in soccer school students. This research method is experimental with randomized control pre-test and post-test group design with different tests in both groups. The sample of football school students and the research location is in the PTPN V Soccer field in Pekanbaru. Participants: 12 active male students aged 14-16 years in one group, given the Neuromuscular Taping application and Core Stability Exercise with jumpers knee pathology, examined and measured with the Agility Illionis Test. Results: the test showed an increase in agility with the Neuromuscular Taping intervention and Core Stability Exercises before the intervention 21.33 ± 1.403 and the mean value after the intervention 14.70 ± 0.815 in one group and Test the research hypothesis using Paired Samples Test with significant results P = 0.000 (P<0.05) with a mean value of 6,631 ± 1,037. The conclusion is the application of Neuromuscular Taping and Core Stability Exercises can increase agility in jumpers knee conditions of PTPN V Pekanbaru soccer school students.